La metafisica nell’ottica di Edith Stein: interdisciplinarità e transdisciplinarità del metodo teologico - Del Gaudio S.F.I., Daniela (Alpha Omega, 2021)
Summary: The study analyses ‘Steinian’ anthropology from an inter-disciplinary and from a trans-disciplinary perspective, showing how philosophy and theology can describe the human person by means of the relationship with the personal being of God, which makes it possible to understand not only the person’s physical, psychological and spiritual characteristics, but also their interior dynamism, their being, their metaphysical reality and their dignity as imago Dei. In the revelation of the person-being of God, which is originary and determinative for the personal being of the human being, there is revealed, in fact, their being a person who is free, spiritual, individual, rational and autonomous because created in his image and likeness. The inter-disciplinary reflection of Edith Stein, from this perspective, investigates the unity of the human being and their multi-dimensional reality in relation to the being of God as one and three, but also in relation to their own creaturely reality, founded upon the mystery of Christ, whose redemptive sacrifice restores to the human being who has fallen through original sin their original dignity and enables the human being to realise their vocation of love in tis fulness, as self-possession and as self-gift, towards God, towards others and towards creation.